Strengthening The Nation Character for Students in Border Area - Aunurrahman Aunurrahman (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to obtain information about strengthening national character for students in the border area, with a focus on the assessment of strengthening programs, program specificities, the actualization of program implementation, and monitoring patterns, monitoring, evaluation and follow-up of character strengthening programs for students in the border area. The study was conducted by combining quantitative and qualitative approaches through data deepening of students in two Senior High Schools (SMA) in border areas, namely SMA Negeri I and SMA Negeri II Balai Karangan, Sanggau district. Through questionnaires, in-depth interviews and Focus Group Discussions (FGD) it was concluded that the general character strengthening program had been carried out quite well, which was marked by a character strengthening program, schools had good initiatives in developing student character strengthening programs, education character has been carried out through the learning process and outside the learning process. Observation, monitoring, evaluation, and follow-up can already be implemented in character strengthening programs for students in the border area. The main supporting factor in the implementation of character strengthening is that there has been a good synergy between schools, parents and the community in character strengthening program in the border areas. Dimensions that have not been optimal are the absence of specific programs that characterize character reinforcement for students in the border area, program socialization has not been carried out thoroughly and the involvement of parents in the discussion of the results of monitoring and evaluation that is not optimal.